2016
DOI: 10.1371/journal.pbio.1002582
|View full text |Cite
|
Sign up to set email alerts
|

A Low-Correlation Resting State of the Striatum during Cortical Avalanches and Its Role in Movement Suppression

Abstract: During quiet resting behavior, involuntary movements are suppressed. Such movement control is attributed to cortico-basal ganglia loops, yet population dynamics within these loops during resting and their relation to involuntary movements are not well characterized. Here, we show by recording cortical and striatal ongoing population activity in awake rats during quiet resting that intrastriatal inhibition maintains a low-correlation striatal resting state in the presence of cortical neuronal avalanches. Involu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
34
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(43 citation statements)
references
References 93 publications
(150 reference statements)
7
34
1
Order By: Relevance
“…Similar manipulations in the limbic part of the striatum lead to hyperactivity expressed as increased normal behavior, which is nonspecific to a body part and is expressed bilaterally. Disinhibition of the sensorimotor territory in the striatum was shown to lead to the appearance of LFP spikes and phase-locked individual neuronal activity which were correlated with the appearance of individual tics (Bronfeld et al, 2013;Israelashvili and Bar-Gad, 2015;Pogorelov et al, 2015;Klaus and Plenz, 2016). The timing of individual LFP spikes was correlated with unitary behavioral events, individual tics, resembling the correlation to individual movement terminations in the current study.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Similar manipulations in the limbic part of the striatum lead to hyperactivity expressed as increased normal behavior, which is nonspecific to a body part and is expressed bilaterally. Disinhibition of the sensorimotor territory in the striatum was shown to lead to the appearance of LFP spikes and phase-locked individual neuronal activity which were correlated with the appearance of individual tics (Bronfeld et al, 2013;Israelashvili and Bar-Gad, 2015;Pogorelov et al, 2015;Klaus and Plenz, 2016). The timing of individual LFP spikes was correlated with unitary behavioral events, individual tics, resembling the correlation to individual movement terminations in the current study.…”
Section: Discussionsupporting
confidence: 75%
“…In addition, disinhibition of the NAc shell led to emotional dysregulation (Stratford and Kelley, 1997;Lopes et al, 2012), which may contribute indirectly to the observed changes in locomotion. Multiple different hyperkinetic states have been evoked using similar manipulations in the sen-sorimotor basal ganglia: disinhibition of the sensorimotor striatum leads to motor tics (Tarsy et al, 1978;McCairn et al, 2009;Bronfeld et al, 2013;Pogorelov et al, 2015;Klaus and Plenz, 2016), downstream disinhibition in the sensorimotor GPe leads to chorea (Grabli et al, 2004;Bronfeld et al, 2010) and disinhibition of the striatum in cats (Yamada et al, 1995), and the motor thalamus in primates (Guehl et al, 2000) leads to dystonia. The disinhibition of sensorimotor territories share common properties: they lead to the expression of different hyperkinetic symptoms in the form of abnormal movements, which are not part of the normal animal's repertoire, are specific to body part, and are expressed unilaterally contralateral to the injected hemisphere.…”
Section: Discussionmentioning
confidence: 99%
“…The diffusion coefficient of all other molecules was set to D* ϭ 5e-8 cm 2 /s (Li et al, 2015). The initial conditions (Table 6) and reactions (Table 7) were modeled according to the kinetic schemes reported by Fernandez et al (2006) to which we added new reactions for pDARPP-32 S97 . Briefly, DARPP-32 is phosphorylated in position T34 by the cAMP-dependent protein kinase A (PKA; pDARPP-32 T34 ), in position T75 by the cyclindependent kinase 5 (CdK5; pDARPP-32 T75 ), in position S97 by casein kinase 2 (CK2; pDARPP-32 S97 ), and in position S130 by casein kinase 1 (CK1; pDARPP-32 S130 ).…”
Section: Computer Modelingmentioning
confidence: 99%
“…We tested directly the hypothesis that EAAC1 controls striatal function ex vivo by obtaining extracellular field recordings in acute brain slices containing the DLS, a domain of the striatum specifically implicated with habit learning (Barnes et al, 2005;Yin et al, 2005;Yin et al, 2006). We stimulated excitatory synaptic afferents by positioning a bipolar stimulating electrode in the DLS 100 -200 m away from the recording electrode ( Fig.…”
Section: Eaac1 Shapes Synaptic Transmission and Plasticity In The Strmentioning
confidence: 99%
See 1 more Smart Citation